Project valuation using state contingent claims - Lally, Martin (School of Management Working Papers, 1992)
This paper shows that the Banz and Miller framework for project valuation, using matrices of state contingent claim prices, is valid only if expectations of future payoffs are not revised. The appropriate general framework when such expectations are revised is then presented, followed by a computationally simpler version.